Mechanobiology-informed biomaterial and tissue engineering strategies for influencing skeletal stem and progenitor cell fate - Woodbury, Seth M.; Swanson, W. Benton; Mishina, Yuji (Frontiers in Physiology, 2023)
Skeletal stem and progenitor cells (SSPCs) are the multi-potent, self-renewing cell lineages that form the hematopoietic environment and adventitial structures of the skeletal tissues. Skeletal tissues are responsible for a wide range of physiological functions because of the large differentiation capacity of SSPCs. The mechanical loading forces and physical properties of the microenvironments in skeletal tissues help guide the differentiation fates of SSPCs due to their evolved ability to sense and transduce physical signals from the environment. To this end, this review first highlights important biomolecules involved with the mechanobiology of SSPCs. It is paramount to study SSPC mechanobiology and account for these mechanics-mediated behaviors when developing tissue engineering therapies to repair and regenerate skeletal tissues. Biomaterials-based tissue engineering approaches provide important tools to study SSPC mechanobiology and control skeletal tissue development because they present a method to grow cells in-vivo or in-vitro using controlled physical environments with measurable physical properties. This review focuses on how the static and dynamic physical properties of different biomaterials and tissue engineering strategies influence the biological fates of SSPCs. Ultimately, taking advantage of the mechanobiology of SSPCs with customizable biomaterial constructs presents a powerful method to predictably guide bone and skeletal organ regeneration.